A tecnologia de intervenção grupal em sala de espera em um serviço de saúde mental - Fonseca, Juliana Macedo Melo da (2014)
Search descriptive-exploratory qualitative approach of the convergent type developed in a Psychosocial Care Center Alcohol and Drugs (CAPSad) in the state of Goiás, in which participants were users of the service. Aimed to evaluate the technology group intervention in the waiting room as a strategy for care. Data collection occurred from February to May 2013, through three ways: participant observation groups in the waiting room; instrument check-list type based on the Q-sort of therapeutic factors described by Yalom (1975); individual interviews with group participants waiting room. The study included 160 people. The data were subjected to thematic analysis according to the assumptions of Lüdke and Andre (1986), with the aid of ATLAS.ti 6.2 software. Results are presented as two papers: Nursing intervention in the waiting room: a successful experience and Evaluation of group technology in the waiting room in a mental health service. The results showed that the technology group in the waiting room provided moments of reflection, knowledge, learning, listening and exchanges. Helped to elucidate the relationship between the theoretical knowledge with practical assistance on structuring and functioning of groups in the waiting room. Shown to be a potential and valuable for the development of educational and support coordinated by the nurse, users of a mental health service space. Was also identified by the presence of all therapeutic factors investigated in perspectives, service user and professionals who conducted the service in the waiting room. Thus, the intervention group in the waiting room favored the action of certain therapeutic factors that helped participants in coping with crisis situations and also allowed the exercise of citizenship, freedom of expression and the coexistence of different and also therapeutic opportunities for treatment and health education.